2014
DOI: 10.1371/journal.pone.0087009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Comparison of 99mTc Exametazime and 123I Ioflupane SPECT in Patients with Chronic Mild Traumatic Brain Injury

Abstract: BackgroundThis study evaluated the clinical interpretations of single photon emission computed tomography (SPECT) using a cerebral blood flow and a dopamine transporter tracer in patients with chronic mild traumatic brain injury (TBI). The goal was to determine how these two different scan might be used and compared to each other in this patient population.Methods and FindingsTwenty-five patients with persistent symptoms after a mild TBI underwent SPECT with both 99mTc exametazime to measure cerebral blood flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
(56 reference statements)
1
11
0
Order By: Relevance
“…The default mode network (DMN), consisting of the inferior orbital frontal cortex, anterior cingulate gyrus, posterior cingulate gyrus, hippocampus, precuneus, superior parietal lobe, and angular gyrus (Buckner et al 2008 ), shows hyperperfusion in patients diagnosed with PTSD and hypoperfusion in patients diagnosed with TBI (Erickson et al 2014 ; Dubroff and Newberg 2008 ; Newberg and Alavi 2003 ; Newberg et al 2014 ; Liu et al 2013 ). By further elucidating the correlation between increased perfusion in DMN structures in PTSD and decreased perfusion in TBI, clinicians may be able to more reliably diagnose PTSD from TBI.…”
Section: Introductionmentioning
confidence: 99%
“…The default mode network (DMN), consisting of the inferior orbital frontal cortex, anterior cingulate gyrus, posterior cingulate gyrus, hippocampus, precuneus, superior parietal lobe, and angular gyrus (Buckner et al 2008 ), shows hyperperfusion in patients diagnosed with PTSD and hypoperfusion in patients diagnosed with TBI (Erickson et al 2014 ; Dubroff and Newberg 2008 ; Newberg and Alavi 2003 ; Newberg et al 2014 ; Liu et al 2013 ). By further elucidating the correlation between increased perfusion in DMN structures in PTSD and decreased perfusion in TBI, clinicians may be able to more reliably diagnose PTSD from TBI.…”
Section: Introductionmentioning
confidence: 99%
“…Specially, the increased CBF in the right ITG was found to be negatively correlated with the attention scores in acute mTBI patients, which may explain the deficits of some cognitive function in mTBI. Contrarily, Newberg et al identified significantly lower CBF levels in the right temporal lobes of mTBI patients using SPECT [36]. In addition, one study found that children with mTBI with persistent posttraumatic symptoms had more severe medial temporal lobe hypoperfusion than those without persistent posttraumatic symptoms [37].…”
Section: Discussionmentioning
confidence: 99%
“…Among these were six healthy patients, 102 patients with mild PD (HYS Stage 1 to Stage 3), and 94 patients with severe PD (HYS Stage 4 and Stage 5) [5,17,18]. A three-dimensional method was used to estimate the features, including skewness, kurtosis, Cyhelsky’s skewness coefficient, Pearson’s median skewness, DAT activity volume, and DAT activity maximum, in the images of activity distribution and striatal activity volume [14,19,20]. Subsequently, the reports were randomly allocated into two groups, each containing 101 reports.…”
Section: Materials and Methodologymentioning
confidence: 99%